Increasing the Production of Opak Semprong with Appropriate Technology to Break the International Market - Siburian, Paningkat; Fridiarty, Lelly; Harahap, Khairunnisa; Purba, Rasita (Universitas Negeri Medan, 2023)
Processing of cassava for the manufacture of opaque semprong products in Melati Kebun Village, Pegajahan District, Serdang Bedagai Regency is in dire need of appropriate technology because the equipment used still has limitations by using human labor, so the process is less efficient, less productive and marketing is limited. In connection with that, in order to help the community managing Small and Medium Enterprises (SMEs), the Cassava Opak Semprong Business PKM was carried out and the Design of Pressing Machines and Spinner Machines was carried out to increase the production of various opaque products in the village. The approach method used is the method of education, production training, machine design/assistance, business management training and marketing. At the end of the PKM Program, partners are able to apply TTG in the opaque production process, carry out bookkeeping, recording and financial reporting in accordance with accounting standards, conduct e-commerce (business transactions via electronic/internet networks), digitally (online) marketing on social media, so that the small and medium enterprises have increased production and get additional net profit and marketing to Malaysia